EVALUASI SENSORIROTI MANIS DENGAN PENAMBAHAN PATI SAGU TERMODIFIKASI SECARA MIKROBIOLOGIS - Septi ' Hidayati; Yusmarini ' '; Rahmayuni ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Modified sago starch (mosas) is sago starch which has been modified microbiology by Lactobacillus plantarum RN2-12112. Mosas be able use for substituent of manufacture sweet bread. The purpose of this study is obtained the modified sago starch by microbiology useLactobacillus plantarum RN2-12112 andgettingthe ratio of flour and mosassweet bread with the best quality standard. This study use a completely randomized design (CRD) with five treatments and three replications, followed by DNMRT test at 5% level. The treatment for this study is S0 (100% flour), S1 (70% flour and 30% mosas), S2 (65% flour and 35% mosas), S3 (60% flour and 40% mosas), S4 (55% flour and 45% mosas).The results of percentage of use flour and mosassignificantly to hedonic color, texture, taste and overall, but did not significantly influence the descriptive color, flavor of sweet bread. Overall acceptance test indicated that the panelists were“rather like to like”for sweet bread. The best treatment based on the sensory evaluation was treatment S2. Keywords:starch modification, lactic acid bacteria, wheat flour, sweet bread.